2021
DOI: 10.5483/bmbrep.2021.54.4.255
|View full text |Cite
|
Sign up to set email alerts
|

Lin28a ameliorates glucotoxicity-induced β-cell dysfunction and apoptosis

Abstract: An excessive and prolonged increase in glucose levels causes β-cell dysregulation, which is accompanied by impaired insulin synthesis and secretion, a condition known as glucotoxicity. Although it is known that both Lin28a and Lin28b regulate glucose metabolism, other molecular mechanisms that may protect against glucotoxicity are poorly understood. We investigated whether Lin28a overexpression can improve glucotoxicity-induced β-cell dysregulation in INS-1 and primary rat islet cells. INS-1, a rat insulinoma … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…As all these above-mentioned mechanisms are downstream effectors, more researchers are looking for the common 'keys' to these mechanisms, namely their upstream regulators, that acts as a master regulatory factor to the development and progression of DM and its complications. Recent studies have then found that RNA binding proteins (RBPs) such as human antigen R (HuR) and TTP (Tristetraprolin) are directly involved in vasculopathy in diabetes or diabetic complications by regulating the expression and stability of vascular endothelial growth factor (VEGF) mRNA [ [16] , [17] , [18] ], while LIN28 mediates the handling and ripening of let7 microRNA (miRNA), which promotes the uptake of blood glucose by tissue cells to inhibit the progression of DM and its complications [ [19] , [20] , [21] ].…”
Section: Introductionmentioning
confidence: 99%
“…As all these above-mentioned mechanisms are downstream effectors, more researchers are looking for the common 'keys' to these mechanisms, namely their upstream regulators, that acts as a master regulatory factor to the development and progression of DM and its complications. Recent studies have then found that RNA binding proteins (RBPs) such as human antigen R (HuR) and TTP (Tristetraprolin) are directly involved in vasculopathy in diabetes or diabetic complications by regulating the expression and stability of vascular endothelial growth factor (VEGF) mRNA [ [16] , [17] , [18] ], while LIN28 mediates the handling and ripening of let7 microRNA (miRNA), which promotes the uptake of blood glucose by tissue cells to inhibit the progression of DM and its complications [ [19] , [20] , [21] ].…”
Section: Introductionmentioning
confidence: 99%
“…The most upregulated DEGs involved in this process, RELN, was predicted to be targeted by hsa-miR-429. Also, one of the most important DEGs for the neuron proliferation is LIN28A [38], which has been reported to ameliorate β-cell dysfunction and apoptosis [39]. LIN28A was targeted in our study by several DEmiRs such as hsa-let-7d-5p, hsa-miR-4510, hsa-miR-329-3p, hsa-miR-296-5p, and hsa-miR-181c-5p, which were downregulated in FOXA2 −/− islets.…”
Section: Resultsmentioning
confidence: 99%
“…CASP3 is a key zymogen in cell apoptosis. It has been reported to be increased in glucotoxicity-induced β-cell apoptosis 45 . All these targets have verified link with the pathogenesis of T2DM.…”
Section: Discussionmentioning
confidence: 99%